Transperineal ultrasonography: First level exam in IBD patients with perianal disease. Issue 8 (August 2016) - Terracciano, Fulvia; Scalisi, Giuseppe; Bossa, Fabrizio; Scimeca, Daniela; Biscaglia, Giuseppe; Mangiacotti, Michele; Valvano, Maria Rosa; Perri, Francesco; Simeone, Anna; Andriulli, Angelo
Abstract: Background: A pelvic magnetic resonance imaging (MRI) represents the front-line method for evaluating perianal disease in patients with inflammatory bowel disease (IBD). Recently, transperineal ultrasonography (TPUS) has been proposed as a simple, safe, time-sparing and useful diagnostic technique to assess different pathological conditions of the pelvic floor. Aim: The aim of this prospective single centre study was to evaluate the accuracy of TPUS versus MRI for the detection and classification of perineal disease in IBD patients. Methods: From November 2013 to November 2014, 28 IBD patients underwent either TPUS or MRI. Fistulae and abscesses were classified according to Parks' and AGA's classification methods. A concordance was assessed by k statistics. Results: Overall, 33 fistulae and 8 abscesses were recognized by TPUS (30 and 7 by MRI, respectively). The agreement between TPUS and MRI was 75% according to Parks' classification ( k  = 0.67) and 86% according to AGA classification ( k  = 0.83), while it was 36% ( k  = 0.34) for classifying abscesses. Conclusions: TPUS proved to be as accurate as MRI for detecting superficial and small abscesses and for classifying perianal disease. Both examinations may be performed at the initial presentation of the patient, but TPUS is a cheaper, time-sparing procedure. The optimal use of TPUS might be in follow-up patients.